A lateral flow immunosensor for direct, sensitive, and highly selective detection of hemoglobin A1c in whole blood - Ang, S.H.; Thevarajah, T.M.; Woi, P.M.; Alias, Y.; Khor, S.M. (Elsevier, 2016)
An immunosensor that operates based on the principles of lateral flow was developed for direct detection of hemoglobin A1c (HbA1c) in whole blood. We utilized colloidal gold-functionalized antibodies to transduce the specific signal generated when sandwich immuno-complexes were formed on the strip in the presence of HbA1c. The number and intensity of the test lines on the strips indicate normal, under control, and elevated levels of HbA1c. In addition, a linear relationship between HbA1c levels and immunosensor signal intensity was confirmed, with a dynamic range of 4-14% (20-130 mmol mol-1) HbA1c. Using this linear relationship, we determined the HbA1c levels in blood as a function of the signal intensity on the strips. Measurements were validated using the Bio-Rad Variant II HPLC and DCA Vantage tests. Moreover, the immunosensor was verified to be highly selective for detection of HbA1c against HbA0, glycated species of HbA0, and HbA2. The limit of detection was found to be 42.5 μg mL-1 (1.35 mmol mol-1) HbA1c, which is reasonably sensitive compared to the values reported for microarray immunoassays. The shelf life of the immunosensor was estimated to be 1.4 months when stored at ambient temperature, indicating that the immunoassay is stable. Thus, the lateral flow immunosensor developed here was shown to be capable of performing selective, accurate, rapid, and stable detection of HbA1c in human blood samples.